National legislative and regulatory activities (OECD Publishing, 2011)
Belgium - Amendment of the Act on classification and security clearances, certifications and security notifications Czech Republic - Resolution of the government of the Czech Republic on the time schedule of preparatory works for enlarging the nuclear power plant Temelín Finland - Temporary Amendment to the Nuclear Liability Act Ireland - Merchant Shipping Act Romania - Emergency Ordinance on the identification, designation and protection of critical infrastructures Emergency Ordinance on the control regime of dual-use items Amendment to the Act on the safe conduct of nuclear activities Nuclear safety norms on design and construction of nuclear power plants and nuclear safety norms on siting of nuclear power plants United Kingdom - Establishment of the Office for Nuclear Regulation United States - Waste Confidence Decision and Rule Update Response to recent events in Japan